2006
DOI: 10.2500/ajr.2006.20.2955
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Tubing after Endoscopic Dacryocystorhinostomy: Is it Necessary?

Abstract: In our retrospective study no significant statistical differences were seen between the patients with stenting compared with patients without stenting. However, prospective, randomized studies are clearly needed to answer the question of whether the use of stents is advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 19 publications
(23 reference statements)
2
34
0
1
Order By: Relevance
“…The necessity of silicone tubing after endoscopic DCR is controversial (23). In almost all past studies, however, silicone tubes were inserted after lacrimal canalicular surgery to prevent postsurgical restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of silicone tubing after endoscopic DCR is controversial (23). In almost all past studies, however, silicone tubes were inserted after lacrimal canalicular surgery to prevent postsurgical restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Accidental or early removal of stents, prior to 2 months, has been cited as a cause for failure [21]. Other papers have shown no diVerence in outcome with or without stenting [24][25][26][27]. With this in mind, Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Though Smirnov [13,14] in his initial study mentioned a higher success rate with stenting, he subsequently corrected his own observations after 2 years and demonstrated that silicone stenting is unnecessary as his success rate with or without silicone tube was 78 and 100 % respectively. Unlu et al [15] further had similar results (84.2 % with stenting and 94.7 % without stenting).…”
Section: Discussionmentioning
confidence: 99%